Paediatric hospital admissions for psychiatric and psychosocial reasons during the first year of the COVID-19 pandemic. (17th February 2022) - McDonnell, T.; Conlon, C.; McNicholas, F.; Barrett, E.; Barrett, M.; Cummins, F.; Hensey, C.; McAuliffe, E.; Nicholson, E.
Abstract: Increases in youth psychiatric presentations to out-patient and emergency department settings during COVID-19 have been reported. This study, using data from five hospitals in Ireland, examines changes in the number and type of paediatric admissions during COVID-19 (March 2020 – February 2021) compared to the previous two years. ICD-10 classification was used to establish admissions with mental, behavioural, neuro-developmental disorders and psychosocial reasons (MBN-PS). Overall hospital admissions fell by 25.3%, while MBN-PS fell by only 2.6%, mostly during an initial lockdown. Admissions for MBN-PS increased in July-August (9.2%), increased further in September-December (28.3%), returning to pre-COVID-19 levels in January–February 2021. Significant increases were observed among youths with anorexia nervosa (47.8%), other eating disorders (42.9%), and admissions for anxiety (29.6%), with these effects relating to females only. Although admissions for self-harm increased (3%) and rates of ASD admissions reduced (17%), these were not statistically significant. The disproportionate increase in admissions for MBN-PS compared to medical admissions suggests an adverse effect of COVID-19 on youth mental health, for females in particular, and supports previous reports of a pandemic specific increase in eating psychopathology. Combined community and acute service delivery and capacity planning are urgently needed given the prior underfunding of services pre-pandemic.